ANALISIS BEBAN KERJA TERHADAP KEBUTUHAN PEGAWAI ADMINISTRASI DALAM MENJAMIN OPTIMALISASI OPERASIONAL AKADEMIK - Yusuf Yusuf; Anfas Anfas (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2016)
The number of employees needs to be based on the workload of administrative staff UPBJJ-UT Ternate. To calculate the activity time employees who used to work and time are not, researchers using work sampling table. Methods of calculating labor requirements are based on the calculation of the workload with the approach per duties of office according MenPAN No. KEP/75/M.PAN/7/2004 on Guidelines for Employee Needs Calculation based Workload in the framework of preparation of formation of civil servants. Samples were UPBJJ-UT Ternate employee status with the principal administrative officer jobs based Target Achievement Quality Employees (CSKP). Calculation and data processing using Microsoft Excel. The study concluded that there is a significant result in the use of working time and to have the results of the number of employees needed for the actual number of employees, it is known that there are 7 functions of employees, unit administrative KTU has an excess number of employees as much as 1 employee and BPP has a shortage of employees as many as 1 employee. For registration and testing PDA unit has a shortage of the number of employees as much as 1 employee.